2013
DOI: 10.1111/jjns.12019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of baby oil on pruritus, sleep quality, and quality of life in hemodialysis patients: Pretest–post‐test model with control groups

Abstract: It was found in this study that administration of baby oil had positive effects on itching, quality of life, and sleep quality in HD patients who had itching complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 32 publications
3
42
0
5
Order By: Relevance
“…As regards pruritus related sleep disability, findings of the current study reported that the highest percentage of study participants complained from pruritus that disturb sleep. The current study coincides with [30] who found that the majority of participants reported that they had sleeping problems at night. Morever [40] reported that nocturnal pruritus is common in patients under hemodialysis and negatively affects sleep quality.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As regards pruritus related sleep disability, findings of the current study reported that the highest percentage of study participants complained from pruritus that disturb sleep. The current study coincides with [30] who found that the majority of participants reported that they had sleeping problems at night. Morever [40] reported that nocturnal pruritus is common in patients under hemodialysis and negatively affects sleep quality.…”
Section: Discussionsupporting
confidence: 91%
“…From the investigators' point of view, the schedule of the majority of study participants maintained that make dialysis for four hours in each session three times per week that help the hemodialysis patients to improve the patients clinical outcomes as evidenced by literature. This finding is in the stream with [30] reported that the majority of the study participants adhere to hemodialysis sessions three times per week.…”
Section: Discussionsupporting
confidence: 69%
“…Xerosis is found in most patients with ESRD and frequently aggravates pruritus. 20,41 Skin hydration with aqueous cream emollient 41 and baby oil 42,43 both have been shown to reduce skin dryness and the severity of UP effectively and to improve patient quality of life when applied two to four times daily. In addition to skin hydration, other topical agents have been used with some success to treat pruritus.…”
Section: Treatmentmentioning
confidence: 99%
“…Therefore, the cornerstone of uremic pruritus therapy is adequate skin hydration. Skin hydration with aqueous cream emollient 73 and baby oil 74,75 have both been demonstrated to effectively reduce skin dryness and the severity of uremic pruritus and improve patient QoL when applied 2 to 4 times daily. There are several small placebo-controlled trials that have shown a significant benefit in uremic pruritus with capsaicin cream, 0.025% to 0.03%, applied 2 to 4 times per day to affected areas.…”
Section: Uremic Pruritusmentioning
confidence: 99%
“…7274,77–80,82,8593,95,96 BUN, blood urea nitrogen; GFR, glomerular filtration rate; PTH, parathyroid hormone; UP, uremic pruritus.…”
Section: Figurementioning
confidence: 99%